Structural, Electrical, and Optical Properties of PbTe Thin Films Prepared by Simple Flash Evaporation Method. (11th September 2012) - Kungumadevi, Lakshmanan; Sathyamoorthy, Ramakrishnan
Abstract : Lead telluride (PbTe) films have been prepared on glass substrates by flash evaporation method. Structure of the film is found to possess stable face-centered cubic (fcc) NaCl phase in which the grains predominantly grow in the direction of (200) plane. The calculated grain size was in the range 19 nm. The electrical resistivity as a function of temperature was measured using four-probe technique. The electrical conductivity was calculated, and the value is found to be from 67.11 to 344.82 S/cm in the temperature range 303–453 K. The value of mobility was evaluated, and it is found to be 0.329 × 10 - 3 cm 2 · V − 1 S − 1 . An optical study reveals that the PbTe thin films exhibit large blue shift. The optical constants such as absorption coefficient and refractive index have been estimated, and the results are discussed.